2019
DOI: 10.3389/feart.2019.00240
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Magnesium, Silicon, and Calcium Isotopes to Rapidly Uplifting and Weathering Terrains: South Island, New Zealand

Abstract: Silicate weathering is a dominant control on the natural carbon cycle. The supply of rock (e.g., via mountain uplift) has been proposed as a key weathering control, and suggested as the primary cause of Cenozoic cooling. However, this is ambiguous because of a lack of definitive weathering tracers. We use the isotopes of the major cations directly involved in the silicate weathering cycle: magnesium, silicon and calcium. Here we examine these isotope systems in rivers draining catchments with variable uplift r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 119 publications
(211 reference statements)
5
17
0
Order By: Relevance
“…As a regional river originating from the Tibetan Plateau, the Jinsha River has the same Ca isotopic range as rivers from the High Himalayan Crystalline Series (HHCS) (0.69-0.92‰), which is lower than some Ca isotopic values in rivers draining dolostone from Lesser Himalayan Series (LHS) (0.99-1.41‰), but higher than some values in rivers draining limestone from Tethyan Sedimentary Series (TSS) (0.50-1.30‰)(Tipper et al, 2008). The δ 44/40 Ca values of the Jinsha River are also consistent with greywacke-draining rivers from the Southern Alps, New Zealand (0.50-1.40‰)(Moore et al, 2013;Pogge von Strandmann et al, 2019b). When compared with other small monolithologic river catchments, the Ca isotopic composition of the Jinsha River is lower than rivers draining granite in La Ronge (1.16-1.33‰)…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…As a regional river originating from the Tibetan Plateau, the Jinsha River has the same Ca isotopic range as rivers from the High Himalayan Crystalline Series (HHCS) (0.69-0.92‰), which is lower than some Ca isotopic values in rivers draining dolostone from Lesser Himalayan Series (LHS) (0.99-1.41‰), but higher than some values in rivers draining limestone from Tethyan Sedimentary Series (TSS) (0.50-1.30‰)(Tipper et al, 2008). The δ 44/40 Ca values of the Jinsha River are also consistent with greywacke-draining rivers from the Southern Alps, New Zealand (0.50-1.40‰)(Moore et al, 2013;Pogge von Strandmann et al, 2019b). When compared with other small monolithologic river catchments, the Ca isotopic composition of the Jinsha River is lower than rivers draining granite in La Ronge (1.16-1.33‰)…”
mentioning
confidence: 75%
“…The correlation between metal isotopic compositions (δ 44/40 Ca, δ 26 Mg) and saturation indices of carbonates could indicate carbonates precipitation (Fan et al, 2016;Hindshaw et al, 2013;Moore et al, 2013;Pogge von Strandmann et al, 2019a;Pogge von Strandmann et al, 2019b;Pogge von Strandmann et al, 2019c;Tipper et al, 2008).The positive relationship between riverine δ 44/40 Ca values with CSI and Sr/Ca ratios ( Fig. 8a and b), implies that carbonates precipitation may elevate the Ca isotopic compositions of the Jinsha River waters.…”
Section: Carbonate Precipitationmentioning
confidence: 91%
“…Magnesium serves as the coordinating cation in the molecule of chlorophyll and activates enzymes needed for the synthesis of organic compounds [16]. Data on the isotope composition of Mg ( 26 Mg/ 24 Mg ratios, expressed in δ 26 Mg values) can provide new insights into the biogeochemical cycling of Mg. Studies focusing on the behavior of Mg isotope fractionations in terrestrial ecosystems have been reviewed by [17][18][19][20]. On crystalline bedrock, much of the within-site variability in δ 26 Mg values appears to be driven by inorganic isotope fractionations accompanying the conversion of primary silicates to secondary clay minerals [17].…”
Section: Introductionmentioning
confidence: 99%
“…This presents a contrast to coccolith growth experiments, where the phytoplankton preferentially took up light Mg isotopes (Ra and Kitagawa, 2007). On the other hand, it has been suggested that plants have little overall effect on riverine Mg isotope ratios (Tipper et al, 2012b), although this effect does appear to depend on location and stream size (Pogge von Strandmann et al, 2019b). This may present a difference between laboratory growth experiments and natural samples, and of course, the diatoms that make up a large proportion of the Myvatn phytoplankton may also not fractionate Mg isotopes.…”
Section: Laxa River Outflowmentioning
confidence: 72%